DAMPAK PSIKOLOGIS NARAPIDANA SEUMUR HIDUP DALAM PERUBAHAN PIDANANYA MENJADI PIDANA PERCOBAAN 20 TAHUN - Rico Fitranto; Mitro Subroto (Universitas Halu Oleo, 2021)
A prisoner is someone whose rights and freedoms must be revoked because he has committed a crime. The loss of freedom of freedom, and the things that must be faced in the face of the environment and the new, and having to part with loved ones, as well as relatives, which negatively affects actions. This study aims to determine the psychological development with a life sentence against a criminal change into a 20-year probationary sentence. This writing uses a normative approach using library techniques. Many with life sentences experienced despair and lost hope, the change of sentence to 20 years probation was a second chance that was coveted by the people. In serving the sentence, there are three important parts that have a large enough influence on the condition of a psychologist, namely environmental conditions in prisons, characteristics between individuals and social support.